Investigating the Cost of Losing Customers and the Credibility of the Organization in the Market with the Approach to Supply Chain of Mobile Companies - Donya Jasim Sahib; Nuha Aadl Abdali Al-Tameemi; Naser Mohsin Jebur (International Journal of Supply Chain Management, 2019)
This article seeks to assess the cost of losing customers and, consequently, the credibility of the organization in the target market. For the wider scope of content, supply chain of mobile phone companies are targeted as a community has been evaluated. The results of the survey showed that today's companies should pay more attention to lost customers, and take measures to reduce them. The loss of the customer for any reason imposes an irreparable cost on the company. In the meantime, telecom operators, as an example of the purpose of this study, in terms of having more competition with competitors, will cause the loss of customer to each one to attract the competitor. Unfortunately, you cannot do anything about those customers who leave the field of practice or leave a particular profession. But many things can be done about customers who are missing out for reasons such as inadequate customer service, poor goods, high sales prices, and so on. The company must investigate customers who are missing out for various reasons and provide each one with a solution.